Assessing the Performance of an Integrated Health Information Exchange System Using Unstructured Supplementary Service Data (International Journal of Innovative Research in Computer Science & Technology, 2020)
As budding nations gradually adopt the use  of IT services to store medical records, several healthcare  facilities are still unable to exchange information because of  limited access to high speed internet service and high cost  of operations. Established HIE implementations are  designed to rely primarily on such tools as the internet. As a  result, healthcare facilities in budding nations cannot  embrace HIE to the maximum to accomplish  interoperability. A versatile and flexible HIE system was  developed in this research to accomplish exchange of health  information. The system adapted the technique for direct  exchange of HIE. This technique uses the Unstructured  Supplementary Service Data (USSD) as the medium for  transmitting encrypted HL7 version 2.X encoded messages  adopting the Signaling System 7 (SS7) exchange  protocol. The system was tested by establishing and  studying a normal situation of communication between two  health facilities that were interacting. The information  recorded included the quality of the message delivery, the  length of the communication and the precision of the  contents of the transmitted message. In conclusion, the  findings indicate a process that relays health information of  patients in Internet-deprived regions in an effective and  safe way. This idea of transmitting encrypted cryptic  messages through USSD can also be applied to several  other fields of study, where the sharing of information is  restricted by poor Internet service availability.
Keywords: Health Information Exchange; Unstructured Supplementary Service Data; Interoperability; Signaling System 7